Hepatitis C viral kinetics in Latino patients: a comparison to African American and Caucasian patients - Maribel Rodríguez-Torres; Juan Burguera; Deana Hallman; José Rodríguez-Orengo; Michelle Echeandia (Annals of Hepatology, 2012)
Introduction. Response to hepatitis C treatment is known to differ by race; and, limited data suggests by ethnicity as well. A lower efficacy of HCV therapy in Latinos has been observed; whether higher doses may improve the response is unknown.Material and methods. This study used the available data from the patients enrolled in the PROGRESS study and stratified it by race and ethnicity. The primary objectives were to evaluate the early viral kinetic pattern in Latino patients and to assess whether it was improved by higher doses of Peg-IFN alfa-2a and/or RBV, as compared to Caucasian and African American patients.Results. From a total of 1145 patients, 51 (4%) were classified Latino, 886 (77%) Caucasian, 124 (11%) African American and 84 (7%) other. Latinos had a similar virological response between the treatment groups at week 4; but by week 12, achieved a greater response with the higher intensified dose of peginterferon alfa-2a, and remained so at week 72. Caucasians had a greater response at week 4 and week 12 with the intensified dose; but by week 72, the response became similar between the treatment groups. The virological responses for African Americans were unaffected by the doses; and by week 12, were lower than both Latinos and Caucasians. In conclusion, this retrospective analysis provides further evidence for racial/ethnic differences in the response to peginterferon alfa-2a (40KD) plus ribavirin therapy in patients with HCV. Although the sample sizes in this analysis are small for generalized conclusions, the findings are of importance to physicians treating Latinos.